Production performance of broiler chickens influenced by feed restriction systems - P, SILAMBARASAN; SAMANTA, R; DAS, T K (The Indian Journal of Animal Sciences, 2012)
An experiment was conducted to evaluate the effect of feed restriction on growth performances of broiler chicken. One hundred fifty two, day old-commercial Hubbard broilers chicks were randomly distributed into 4 treatments. Each treatment included two replicates with 19 birds per replicate. For the first two weeks of life, feed and water were provided ad libitum. At the age of 3 weeks, one group was kept as control (Co) with no feed restriction while the other groups were restricted to access of feed for 4 h (T1, from 10 AM - 2 PM), 6 h (T2, from 10 AM–4 PM) and 8 h (T3 from 10 AM - 6 PM) until the age of 42 days. By restricted time feeding, body weight was significantly decreased but feed conversion ratio was significantly improved in 8 h and 6 h restricted group than control and 4 h restricted group. Restricted time feeding decreased dressed carcass weight but percentage of back, thigh and drumstick yield was significantly improved. Whereas, breast yield and abdominal fat % were decreased relative to control group. It can be concluded that restricted time feeding between 6 to 8 h may be applied in broiler managemental system without a very significant reduction in performance.